Estudo comparativo da reabsorção radicular dos incisivos superiores em pacientes tratados com ortodontia lingual e vestibular - Makluf, Carlos Eduardo Nassif (2017)
This research aimed at comparing the magnitude of external apical root resorption (EARR) in upper incisors in two groups of patients with low to moderate anterior crowding, one treated through lingual orthodontics, and the other, through conventional labial orthodontics. The sample was constituted of 40 patients (28 woman and 12 men aged from 11 to 45), who were divided in two groups, lingual (20 patients) and conventional labial (20 patients). The magnitude of external apical root resorption was measured through periapical x-rays, obtained at the beginning of the treatment (T1) and at the end of the leveling stage (T2). The periapical x-rays were digitized and then transferred to CorelDraw X7, in which radicular lengths were measured. Between T1 and T2, for intragroup and intergroup comparisons, t-paired and independent tests were used respectively. Results showed a statistically significant difference regarding all evaluated teeth. The magnitude of EARR (T2-T1) varied from -0.35mm to -0.63 mm in the lingual group and from -0.66 mm to -0.85mm in the conventional labial group. In the intergroup comparison, no statistically significant difference was found in the magnitude of EARR. In neither of the groups, a tooth with resorption equal or greater than 1 millimitre was found. Therefore, it was concluded that the magnitude of external apical root resorption in upper incisors was similar in both groups, lingual and labial. Both techniques created a clinically insignificant apical rounding